Documentation and Analysis of ICT initiatives of Agricultural Research Institutions in Telangana: Application of Nudge Theory - Shilpa, Bolleboina; Basavaprabhu Jirli (Indian Journal of Extension Education, 2023)
The application of ICT offers excellent possibilities for empowering stakeholders and establishing appropriate communication between research and extension systems. This paper attempts to document and analyze selected ICT initiatives of three Agricultural Research Institutes in Telangana. Nudge Theory, a qualitative tool is employed to identify specific nudges of those initiatives. A relatively new concept, nudge proposes positive reinforcement and indirect suggestions as ways to influence behavior. These are simple, low-cost interventions that alter behavior in predictable ways. A descriptive research design was adopted for the study. A nudging framework was developed and nudges were classified under 8 groups viz., internally imposed- mindful encouraging, mindful discouraging, mindless encouraging, and mindless discouraging and the externally imposed- mindful encouraging, mindful discouraging, mindless encouraging, and mindless discouraging.